RELATIONSHIP OF APOLIPOPROTEIN A-1 GENE POLYMORPHISM WITH SOME GROWTH TRAITS OF COMMON CARP (CYPRINUS CARPIO L .) - Abdulmajeed, Othman M.; Al-Khshali, Mohammad S.; Al Ameri, Ahmed W. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
The study was conducted to investigate the relationship between the polymorphisms of A, B, C, D and E of the apolipoprotein A-1 (ApoA-1) gene with some traits (daily and total weight gain rate and feed conversion rate and efficiency) in 70 samples of common carp (Cyprinus carpio). There were significant differences in the growth traits of the genotypes A, B, C and D of the apolipoprotein A-1 gene compared to the genotype E. The results showed that the genotype C was significantly superior (p≤0.05) in the daily and total weight gain rates and reached the highest value of 0.56 and 39.42 g/fish, respectively, while the genotype E decreased to the lowest value of 0.14 and 9.50 g/fish, respectively. On the other hand, the feed conversion rate recorded highest significant effect (p≤0.05) at the genotype C and reached 5.13 Compared with the E genotype which recorded 9.6, the highest significant effect (p≤0.05) on the feed conversion efficiency trait was at the C genotype at a rate of 19.49% compared to the E genotype which reached 10.41%. We conclude from the above that the ApoA-1 gene may have an effect in improving the productive growth traits in common carp fish through its effect on the quantitative traits associated with the genetic phenotypes.